Optimization of zinc-doped emitter layer thickness and doping concentration for gallium antimonide based thermophotovoltaic cells - Rashid W.E.; Gamel M.M.A.; Ker P.J.; Yao L.K.; Rahman N.A.; Jing L.H.; Jamaludin M.Z. (Akademi Sains Malaysia, 2023)
Gallium antimonide based thermophotovoltaic cell is a well-known photovoltaic diode that can directly convert thermal radiation into electricity. Recent investigations on the improvement of gallium antimonide thermophotovoltaic cell performance have led to a number of optimization studies, particularly on the cell design structures. However, low conversion efficiency of gallium antimonide thermophotovoltaic cell remains a major challenge in this area. An optimization study was previously demonstrated with increased efficiency up to 6.63 % incorporating an optimum emitter thickness of 0.85 ?m. This work extended the optimization possibilities, aiming to achieve higher power conversion efficiency of gallium antimonide thermophotovoltaic cell. Different doping concentrations of the emitter layer ranging from 1x1018 to 5x1020 cm-3 were studied using Silvaco TCAD simulation software. Within the investigated doping concentrations, the optimum power efficiency of 7.51 % was achieved at 1x1020 cm-3 under AM1.5 illumination condition. Additionally, higher cell performance was achieved with a power efficiency of 7.88 % by employing an emitter layer thickness of 0.15 ?m and a doping concentration of 1.7x1020 cm-3. The success of this work will contribute to a perceptive reference for the future development in practical device fabrication of high-performance gallium antimonide thermophotovoltaic cell. 2019, Akademi Sains Malaysia.